Participatory communication as the key to successful disaster management in Pangandaran district - Bakti, Iriana; Zubair, Feliza; Budiana, Heru Ryanto (Jurnal Kajian Komunikasi, 2023)
Background: Pangandaran, situated within the province of West Java, is considered a region susceptible to natural disasters, leading to significant material damages and, unfortunately, loss of human life. This particular calamity has attracted the attention of various stakeholders, encompassing the local government, affiliated organizations, social communities, volunteers, and numerous others. The circumstances mentioned above have led to the development of participatory communication initiatives to promote cooperation in disaster management. Purpose: This study aims to ascertain the factors contributing to heteroglossia, discourse, polyphony, and collaboration among communities and volunteers. Methods: The research method utilized in this study is a descriptive study, incorporating a range of data collection techniques, including in-depth interviews, observation, and literature analysis. Furthermore, to conduct comprehensive data analysis, this study involves data reduction, data display, conclusion derivation, and verification. Moreover, the technique employed for data source identification involves systematically classifying stakeholders, including individuals affiliated with institutions and community members/volunteers who actively participate in collaborative efforts to address disaster-related issues in the Pangandaran Regency. Additionally, the study involved a cohort of five key informants deliberately chosen to represent the community under the study. Results: The study results indicate that, despite differences in tasks, responsibilities, roles, and level of expertise within the community or volunteers, they are willing to exchange knowledge, drawing on their viewpoints openly. Furthermore, the dialogue process that unfolds among the community/volunteers takes the form of a democratic discussion to attain consensus in their respective roles. Conclusion: Communities/volunteers have established collaborative efforts grounded in their understanding, awareness and commitment to assisting individuals affected by adverse circumstances. Moreover, shared norms and beliefs have guided their robust, extensive relationships and networks.